Plant production of high affinity nanobodies that block SARS-CoV-2 spike protein binding with its receptor, human angiotensin converting enzyme - Pitino, Marco; Fleites, Laura A.; Shrum, Lauren; Heck, Michelle; Shatters, Robert G. (Frontiers in Bioengineering and Biotechnology, 2022)
Nanobodies® (VHH antibodies), are small peptides that represent the antigen binding domain, VHH of unique single domain antibodies (heavy chain only antibodies, HcAb) derived from camelids. Here, we demonstrate production of VHH nanobodies against the SARS-CoV-2 spike proteins in the solanaceous plant Nicotiana benthamiana through transient expression and their subsequent detection verified through western blot. We demonstrate that these nanobodies competitively inhibit binding between the SARS-CoV-2 spike protein receptor binding domain and its human receptor protein, angiotensin converting enzyme 2 (ACE2). There has been significant interest and a number of publications on the use of plants as biofactories and even some reports of producing nanobodies in plants. Our data demonstrate that functional nanobodies blocking a process necessary to initiate SARS-CoV-2 infection into mammalian cells can be produced in plants. This opens the alternative of using plants in a scheme to rapidly respond to therapeutic needs for emerging pathogens in human medicine and agriculture.